Preparation method of hollow-section polyacrylonitrile dry-jet wet-spun carbon fiber

By using a spinneret with an annular receptive cavity and suitable solidification bath conditions, the problems of hollow cross-section carbon fiber in the control of inner and outer diameter ratio and density are solved, and high-performance and low-cost carbon fiber preparation is achieved.

CN119465448AActive Publication Date: 2025-02-18ZHONGFU SHENYING CARBON FIBER
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411602136.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

When the existing dry spray wet spinning technology prepares hollow cross-section carbon fibers, it is difficult to effectively control the inner and outer diameter ratio and density of the fibers, resulting in excessive deviations of the fibers and poor density.

Method used

Using a spinneret with an annular consent cavity, the structure of the hollow cross section polyacrylonitrile carbon fiber is effectively controlled by controlling the size of the needle-containing cylinder and the through holes and the aspect ratio of the spinneret holes, and matching the appropriate solidification bath conditions. .

Benefits of technology

The high specific surface area, high density, low core rate, high filling ratio and high wave absorption properties of hollow cross-section carbon fiber are achieved, reducing production costs and suitable for the preparation of a variety of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465448A_ABST
    Figure CN119465448A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of hollow-section polyacrylonitrile dry-jet wet-spun carbon fibers. The method comprises the following steps: extruding a spinning solution through a spinneret plate with an annular accommodating cavity, entering a coagulating bath, carrying out multi-section desalting water washing, hot water drafting, oiling, drying densification and steam drafting, winding and collecting to obtain a precursor with a hollow cross section, pre-oxidizing the precursor with the hollow cross section, and carbonizing in a low-temperature furnace and a high-temperature furnace to obtain the hollow fiber. The dry-jet wet-spun carbon fiber with the hollow section is prepared. The preparation method is simple, the structure of the hollow-section polyacrylonitrile carbon fiber is effectively controlled by controlling the structure of the spinneret plate with the annular cavity and subsequent process conditions, and the prepared hollow-section polyacrylonitrile carbon fiber has the advantages of high specific surface area, low skin-core rate, low cost and the like; the method has wide application prospects in the fields of wave-absorbing materials, electromagnetic shielding materials, resin-based composite materials, carbon / carbon composite materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing hollow cross-section polyacrylonitrile dry-jet wet-spinning carbon fiber, belonging to the technical field of carbon fiber preparation. Background Art

[0002] Hollow fiber is a fiber with a cavity along the axial direction of the cross section. Due to its special cross-sectional shape, the surface area of ​​the hollow cross-sectional fiber is greatly improved compared with the circular cross-sectional fiber, and the composite performance with the matrix is ​​expected to be greatly improved; the cavity in the hollow fiber provides static air, thereby improving the warmth retention of the fiber, increasing the surface area per unit volume, and thus improving the fluffiness of the fiber; the adsorption capacity of the hollow fiber for media such as water, air, and blood, as well as the ability to combine with the matrix material as a composite material, to a certain extent, not only improves the rigidity and stiffness of the fiber, but also improves the bending resistance and wear resistance of the fiber. If the hollow element is filled inside, it is expected to prepare a hollow fiber with certain special functions. At present, the hollow cross-section of the fiber is mainly prepared by melt spinning, electrospinning, wet spinning and other methods. The hollow fiber mainly includes polyester fiber, glass fiber, carbon fiber, nanofiber, etc. Polypropylene (PP), polyester, polyamide, polyacrylonitrile, polystyrene, polyethylene, nylon, cellulose acetate, and various nylon, polyester, acrylic fiber, polypropylene and other chemical materials can be made into hollow fibers through a suitable spinning process.

[0003] Dry-jet wet spinning technology can effectively improve the mechanical properties and spinning speed of polyacrylonitrile fiber. It is an engineering feasible technology. However, the dry-jet wet spinning process is extremely cumbersome. Under the action of surface tension, the forming process of the spinning solution with viscoelastic properties after passing through a special hollow spinneret hole is much more complicated than the forming process after passing through a circular spinneret hole. The spinning solution is extruded and expanded after passing through a special hollow spinneret hole. However, due to the difference in the structure of the hollow spinneret hole, the uneven shearing effect on the solution can easily lead to the breakage of the fine stream. The design of the inner and outer diameters of the spinneret plate is crucial. However, if the difference between the inner and outer diameters is too small, the solution is prone to rupture after extrusion under a large N2 pressure. The hollow fiber is difficult to withstand the strong driving force of the coagulation bath process, and the density becomes poor. If the difference between the inner and outer diameters is too large, the solution is easily bonded into a round solid filament through the air layer after extrusion, resulting in excessive deviation of the hollow fiber. Therefore, it is required that the prepared hollow carbon fiber has a suitable inner and outer diameter ratio. The inner and outer diameter ratio E i Defined as:

[0004]

[0005] The relative deviation S is expressed by the absolute value of the difference between the fiber inner and outer diameter ratio Ei and the spinneret inner and outer diameter E and the ratio of the spinneret inner and outer diameter E:

[0006]

[0007] In the formula, d is the inscribed circle diameter of the hollow cross-section carbon fiber, A1 is the cross-sectional shaded area of ​​the hollow cross-section carbon fiber; D is the circumscribed circle diameter of the hollow cross-section carbon fiber, and A0 is the circumscribed circle area of ​​the fiber. Because of the special surface morphology of the hollow cross-section fiber, oxygen is more likely to penetrate into the interior during the pre-oxidation process. On the one hand, it alleviates the radial unevenness of the fiber, improves the consistency of the pre-oxidized filament, and reduces the skin-core ratio of the carbon fiber; on the other hand, it increases the reaction rate, reduces the wire travel process, reduces the reaction time, reduces the operating temperature of the reactor, realizes the rapid preparation of carbon fiber, and reduces production costs. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing hollow cross-section polyacrylonitrile dry-jet wet-spinning carbon fiber. In the method, the spinning solution is first sprayed out through a spinneret with an annular cavity and then enters a coagulation bath to form a primary fiber with a hollow cross-section. The fiber is washed with desalted water, drawn with water, oiled, dried, and steam-drawn before winding and collecting to obtain a hollow cross-section precursor, which is pre-oxidized and carbonized to obtain a carbon fiber with a hollow cross-section.

[0009] The technical solution for achieving the purpose of the present invention is as follows:

[0010] A method for preparing hollow cross-section polyacrylonitrile dry-jet wet-spun carbon fibers comprises the following steps:

[0011] (1) using 95-99 wt.% acrylonitrile as a first monomer and 1-5 wt.% acrylic acid, methyl acrylate, methyl methacrylate or isobutyl methacrylate as a second monomer, and carrying out solution polymerization in dimethyl sulfoxide to obtain a spinning solution, wherein the temperature of the spinning solution is controlled to be 40-70° C. and the solid content is controlled to be 10-25%;

[0012] (2) After the spinning solution is degassed and debubbled, it is pressurized and extruded through a spinneret with an annular cavity at an extrusion speed of 10 to 20 m / min, and then enters a dimethyl sulfoxide coagulation bath through an air layer for coagulation phase separation to form gel strips, and is simultaneously drawn to obtain primary fibers with a hollow cross-section, the coagulation bath concentration is 30 to 50 wt%, and the coagulation bath temperature is 5 to 20°C; the spinneret with an annular cavity comprises a first plate body 1 and a second plate body 2; the first plate body 1 is provided with a plurality of through holes 4, a plurality of needle-containing cylinders 8, an annular groove 3 is provided on the top, and an annular groove 5 is provided on the bottom; the second plate body 2 is provided with a plurality of through holes 9 containing micropores; the second plate body 2 is provided with a plurality of through holes 9 containing micropores; A plate body 1 and a second plate body 2 are bonded to form a pulp feeding channel 6; the needle-containing cylinder 8 on the first plate body and the micropore through hole 9 on the second plate body correspond to each other to form an annular cavity 7; the through hole 4 is connected to the pulp feeding channel 6, and the pulp feeding channel 6 is connected to the annular cavity 7; the annular groove 3 and the annular groove 5 are installed with rubber rings; the top of the first plate body 1 is against the raw liquid feeding pipeline, and the top of the second plate body 2 is against the bottom of the first plate body 1; the needle length of the needle-containing cylinder 8 is the same as the length of the micropore in the micropore through hole 9, the needle diameter of the needle-containing cylinder 8 is 0.5-0.6mm, and the micropore diameter in the micropore through hole 9 is 1.0-1.5mm; the aspect ratio of the spinneret hole is 3-4:1;

[0013] (3) The nascent fiber is washed with deionized water in multiple stages to remove the solvent, and then washed with hot deionized water and drawn;

[0014] (4) The fibers after hot water drawing are oiled and then passed through hot rollers for drying and densification;

[0015] (5) The dried and densified fibers are steam drawn, and then wound to form hollow-section raw fibers;

[0016] (6) The hollow section raw wire passes through a wire withdrawal rack and enters a pre-oxidation furnace for pre-oxidation to obtain pre-oxidized wire;

[0017] (7) The pre-oxidized filaments are sequentially carbonized in a low-temperature furnace and a high-temperature furnace to prepare a carbon fiber with a hollow cross-section; the temperature of the low-temperature furnace is 580-650°C, and the drafting ratio of the low-temperature furnace is 1.0-1.1 times; the temperature of the high-temperature furnace is 1450-1600°C, and the drafting ratio of the high-temperature furnace is 0.95-1.05 times.

[0018] Furthermore, in step (2), the method for degassing is as follows: first, the spinning solution is degassed in a degassing kettle at a pressure of -76KPa, and then subjected to a 3μm primary filtration treatment, and then subjected to a degassing kettle at a pressure of -97KPa, and then sent to a 1μm secondary filtration treatment.

[0019] Furthermore, in step (2), the air layer height is 1 to 5 mm, and the air drafting multiple is 1 to 2. Preferably, the coagulation bath concentration is 45 wt %, and the coagulation bath temperature is 5°C.

[0020] Furthermore, in step (2), the number of holes in the through hole 4 is 1 to 2K, the number of holes in the needle-containing cylinder 8 and the number of holes in the micropore-containing through hole 9 are the same, both are 1 to 5K, the needle length of the needle-containing cylinder 8 and the length of the micropores in the micropore-containing through hole 9 are both 0.3 to 1.0 mm; the length of the cylinder in the needle-containing cylinder 8 is 10 to 15 mm, and the diameter of the cylinder is 3 to 5 mm; the length of the through hole in the micropore-containing through hole 9 is 5 to 8 mm, the through hole diameter is 4 to 6 mm, and the hole spacing is 1 to 3 mm.

[0021] Furthermore, in step (2), the spinneret having the annular cavity is made of Hastelloy C276, 3161L alloy, 1Cr18Ni9Ti austenitic stainless steel, AISI316 or AISI630.

[0022] Furthermore, in step (3), the water washing tank is 3 to 7 levels, the water washing temperature is 20 to 36°C, and the stretching multiple is 1 to 1.5 times; the hot desalted water washing and stretching are 1 to 3 stages, the temperature is 60 to 80°C, and the stretching multiple is 1 to 2.0 times.

[0023] Furthermore, in step (4), the temperature of the hot roller is level 3 to 7, the temperature range is 100 to 185° C., and the pressure of the hot roller is 0.30 to 1.10 MPa.

[0024] Furthermore, in step (5), the steam pressure is 0.30-0.80 MPa, the steam drawing ratio is 3.0-5.0 times, and the winding speed is 350-500 m / min.

[0025] Furthermore, in step (6), the pre-oxidation temperature is 200°C to 300°C, and the pre-oxidation draft ratio is 0.9 to 1.05 times. Preferably, the pre-oxidation temperature is 220°C to 240°C.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention designs a spinneret with an annular cavity and successfully applies it to the dry-jet wet spinning method to prepare hollow cross-section polyacrylonitrile carbon fibers;

[0028] (2) The present invention achieves effective control of the hollow cross-section polyacrylonitrile carbon fiber structure by controlling the size of the needle-containing cylinder and the micropore through hole in the spinneret with an annular cavity and the aspect ratio of the spinneret hole, while matching appropriate coagulation bath conditions;

[0029] (3) The hollow cross-section carbon fiber prepared by the method of the present invention has the advantages of high specific surface area, high density, low skin-core ratio, high filling ratio, high absorbing performance, high tensile strength, low cost, etc. When used as a two-dimensional reinforcement material, it can load other media to improve the comprehensive performance of the composite material. It is suitable for the preparation of absorbing materials, electromagnetic shielding materials, radar absorbing materials, resin-based composite materials, carbon / carbon composite materials, functional materials, structural materials and stealth weapons. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the overall structure of the spinneret;

[0031] Figure 2 for Figure 1 The local enlarged analysis diagram at point I in the middle;

[0032] Figure 3 is a schematic structural view of the first plate body;

[0033] Figure 4 It is a three-view diagram of the structure of the second plate;

[0034] The reference numerals in the figure are: 1 first plate body, 2 second plate body, 3 annular groove, 4 through hole, 5 annular groove, 6 slurry inlet channel, 7 annular cavity, 8 needle-containing cylinder, 9 microporous through hole. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] like Figures 1 to 4 As shown, the spinneret used in the present invention comprises a first plate body 1 and a second plate body 2; the first plate body 1 is provided with a plurality of through holes 4, a plurality of needle-containing cylinders 8, an annular groove 3 is provided on the top, and an annular groove 5 is provided on the bottom; the second plate body 2 is provided with a plurality of through holes 9 containing micropores; the first plate body 1 and the second plate body 2 are fitted to form a slurry inlet channel 6; the needle-containing cylinders 8 on the first plate body and the micropore-containing through holes 9 on the second plate body correspond to each other to form an annular cavity 7; the through holes 4 are connected to the slurry inlet channel 6, and the slurry inlet channel 6 is connected to the annular cavity 7; the annular groove 3 and the annular groove 5 are installed with rubber rings; the top of the second plate body 2 is against the bottom of the first plate body 1. The top of the first plate body 1 is against the raw liquid feed pipe.

[0037] Specifically, the first plate body 1 has a circular shape. The through holes 4 are evenly distributed along the circumference of the first plate body 1, and the number of through holes 4 is 1 to 2K. The needle-containing cylinder 8 is located inside the through hole 4 and evenly distributed along the center of the first plate body 1, and the number of holes of the needle-containing cylinder 8 is 1 to 5K, the length of the cylinder is 10 to 15 mm, the diameter of the cylinder is 3 to 5 mm, the length of the needle is 0.3 to 1.0 mm, and the diameter of the needle is 0.3 to 0.8 mm.

[0038] Specifically, the second plate body 2 has a circular shape. The number of holes of the microporous through hole 9 is 1 to 5K, the length is 5 to 8 mm, the diameter is 4 to 6 mm, and the hole spacing is 1 to 3 mm; the length of the micropores in the microporous through hole 9 is the same as the needle length of the needle cylinder 8, both of which are 0.3 to 1.0 mm, the diameter of the micropores is 0.5 to 1.5 mm, and the aspect ratio of the spinneret hole is 3 to 5:1.

[0039] Specifically, a rubber ring is installed in the annular groove 3 to seal the connection between the first plate body 1 and the raw liquid feeding pipeline to prevent leakage.

[0040] Specifically, a rubber ring is installed in the annular groove 5 to seal the connection between the first plate body 1 and the second plate body 2 to prevent liquid leakage.

[0041] The top of the first plate body 1 of the spinneret used in the present invention is against the stock solution feed pipe, and the spinning stock solution flows into the through hole 4 through the feed pipe, thereby passing through the first plate body 1, and then flows into the slurry inlet channel 6, and then flows into the annular cavity 7, thereby passing through the second plate body 2 for extrusion to obtain the spinning stock solution with a hollow cross section. The hollow cross-section stock solution is solidified and stretched to form a primary fiber with a hollow cross section, such as Figure 2 As shown, hollow cross-section carbon fiber is obtained through subsequent processes.

[0042] Example 1

[0043] With 96wt% acrylonitrile as the first monomer and 5wt% methyl acrylate as the second monomer, free radical solution polymerization is carried out in dimethyl sulfoxide to obtain a spinning solution, and the temperature of the spinning solution is controlled to be 60°C and the solid content is 20%. The spinning solution is firstly de-singled in a de-singling kettle at a pressure of -76Kpa, and then de-singled by a degassing kettle at a pressure of -97KPa, and then sent to a 1μm secondary filtration for treatment. The spinning solution after the refining treatment is pressurized and transported to the spinning unit. The spinning solution is passed through a 1μm candle wick filter and extruded by a spinneret with an annular cavity after pressurization, and the extrusion speed is 15.49m / min. The spinneret with an annular cavity is made of 316L alloy, the first plate body contains a needle cylinder of 3K, the needle diameter is 0.5mm, the second plate body contains a microporous through hole number of 3K, the microporous aperture is 1.0mm, and the spinneret hole aspect ratio is 3:1. The spinning solution enters the coagulation bath after passing through a 1mm air layer for coagulation and molding. The coagulation bath concentration is 45wt%, the coagulation bath temperature is 5°C, and a drafting multiple of 1.05 is applied to obtain the nascent fiber. The nascent fiber is subjected to multi-stage desalted water at 35°C to remove the solvent, and after washing, it is subjected to hot water at 70°C and is simultaneously drafted at 1.3 times. The fiber after hot water drafting passes through an oil bath with a concentration of 1.10%. The oiled fiber is dried and densified by a hot roller with a temperature gradient of 100 to 185°C, and the drying roller pressure is maintained at 0.55MPa, with 25 drying rollers. The dried and densified fiber bundle is steam-drawn, with a saturated steam pressure of 0.45MPa and a steam drafting multiple of 3.55 times. After steam drafting, it is wound and formed to obtain a hollow cross-section raw fiber. The raw fiber passes through a wire withdrawal rack and enters a pre-oxidation furnace for pre-oxidation. The pre-oxidation temperature is 240°C, and the pre-oxidation drafting multiple is 0.98 times. The pre-oxidized filaments are carbonized in a low-temperature furnace and a high-temperature furnace in turn to prepare carbon fibers with a hollow cross-section. The temperature of the low-temperature furnace is controlled at 600°C, the drafting ratio of the low-temperature furnace is 1.02 times, and the temperature of the high-temperature furnace is controlled at 1500°C, and the drafting ratio of the high-temperature furnace is 1.01 times. The prepared carbon fiber has a skin-core ratio of 3% and an inner-outer diameter ratio of E i The relative deviation is 58% and 16%.

[0044] Example 2

[0045] With 96wt% acrylonitrile as the first monomer and 4wt% acrylic acid as the second monomer, free radical solution polymerization is carried out in dimethyl sulfoxide to obtain a spinning solution, and the temperature of the spinning solution is controlled to be 60°C and the solid content is 20%. The spinning solution is firstly de-singled in a de-singling kettle at a pressure of -76Kpa, and then de-singled by a 3μm primary filtration treatment, and then de-singled by a degassing kettle at a pressure of -97KPa, and then sent to a 1μm secondary filtration for treatment. The spinning solution after the refining treatment is pressurized and transported to the spinning unit. The spinning solution is passed through a 1μm candle wick filter and extruded by a spinneret with an annular cavity after pressurization, and the extrusion speed is 15.49m / min. The spinneret with an annular cavity is made of 316L alloy, the first plate body contains a needle cylinder of 3K, the needle diameter is 0.6mm, the second plate body contains a microporous through hole number of 3K, the microporous aperture is 1.2mm, and the spinneret hole aspect ratio is 4:1. The spinning solution enters the coagulation bath after passing through a 1mm air layer for coagulation and molding. The coagulation bath concentration is 45wt%, the coagulation bath temperature is 5°C, and a drafting multiple of 1.05 is applied to obtain the nascent fiber. The nascent fiber is subjected to multi-stage desalted water at 35°C to remove the solvent, and after washing, it is subjected to hot water at 70°C and is simultaneously drafted at 1.3 times. The fiber after hot water drafting passes through an oil bath with a concentration of 1.10%. The oiled fiber is dried and densified by a hot roller with a temperature gradient of 100 to 185°C, and the drying roller pressure is maintained at 0.55MPa, with 25 drying rollers. The dried and densified fiber bundle is steam-drawn, with a saturated steam pressure of 0.45MPa and a steam drafting multiple of 3.55 times. After steam drafting, it is wound and formed to obtain a hollow cross-section raw fiber. The raw fiber passes through a wire withdrawal rack and enters a pre-oxidation furnace for pre-oxidation. The pre-oxidation temperature is 240°C, and the pre-oxidation drafting multiple is 0.98 times. The pre-oxidized filaments are sequentially carbonized in a low-temperature furnace and a high-temperature furnace to prepare carbon fibers with a hollow cross-section. The temperature of the low-temperature furnace is controlled at 600°C, the drafting ratio of the low-temperature furnace is 1.02 times, and the temperature of the high-temperature furnace is controlled at 1500°C, and the drafting ratio of the high-temperature furnace is 1.01 times. The prepared carbon fiber has a skin-core ratio of 0%, an inner-outer diameter ratio of E i is 55% and the relative deviation is 10%.

[0046] Example 3

[0047] With 95wt% acrylonitrile as the first monomer and 5wt% isobutyl methacrylate as the second monomer, free radical solution polymerization is carried out in dimethyl sulfoxide to obtain a spinning solution, and the temperature of the spinning solution is controlled to be 60°C and the solid content is 20%. The spinning solution is firstly de-singled in a de-singling kettle at a pressure of -76Kpa, and then de-singled by a 3μm primary filtration treatment, and then de-singled by a degassing kettle at a pressure of -97KPa, and then sent to a 1μm secondary filtration for treatment. The spinning solution after the refining treatment is pressurized and transported to the spinning unit. The spinning solution is passed through a 1μm candle wick filter and extruded by a spinneret with an annular cavity after pressurization, and the extrusion speed is 15.49m / min. The spinneret with an annular cavity is made of 316L alloy, the first plate body contains a needle cylinder of 3K, the needle diameter is 0.5mm, the second plate body contains a microporous through hole number of 3K, the microporous aperture is 1.5mm, and the spinneret hole aspect ratio is 3:1. The spinning solution enters the coagulation bath after passing through a 1mm air layer for coagulation and molding. The coagulation bath concentration is 45wt%, the coagulation bath temperature is 5°C, and a drafting multiple of 1.05 is applied to obtain the nascent fiber. The nascent fiber is subjected to multi-stage desalted water at 35°C to remove the solvent, and after washing, it is subjected to hot water at 70°C and is simultaneously drafted at 1.3 times. The fiber after hot water drafting passes through an oil bath with a concentration of 1.10%. The oiled fiber is dried and densified by a hot roller with a temperature gradient of 100 to 185°C, and the drying roller pressure is maintained at 0.55MPa, with 25 drying rollers. The dried and densified fiber bundle is steam-drawn, with a saturated steam pressure of 0.45MPa and a steam drafting multiple of 3.55 times. After steam drafting, it is wound and formed to obtain a hollow cross-section raw fiber. The raw fiber passes through a wire withdrawal rack and enters a pre-oxidation furnace for pre-oxidation. The pre-oxidation temperature is 240°C, and the pre-oxidation drafting multiple is 0.98 times. The pre-oxidized filaments are sequentially carbonized in a low-temperature furnace and a high-temperature furnace to prepare carbon fibers with a hollow cross-section. The temperature of the low-temperature furnace is controlled at 650°C, the drafting ratio of the low-temperature furnace is 1.02 times, and the temperature of the high-temperature furnace is controlled at 1600°C, and the drafting ratio of the high-temperature furnace is 1.01 times. The prepared carbon fiber has a skin-core ratio of 0%, an inner-outer diameter ratio of E i The relative deviation is 40% and 17.6%.

[0048] Example 4

[0049] This embodiment is roughly the same as embodiment 3, except that the raw silk passes through the wire withdrawal rack and enters the pre-oxidation furnace for pre-oxidation, the pre-oxidation temperature is 220°C, and the pre-oxidation drafting multiple is 0.98 times. The pre-oxidation silk is successively carbonized in a low-temperature furnace and a high-temperature furnace to prepare a carbon fiber with a hollow cross-section. The temperature of the low-temperature furnace is controlled at 580°C, the drafting multiple of the low-temperature furnace is 1.02 times, and the temperature of the high-temperature furnace is controlled at 1450°C, and the drafting multiple of the high-temperature furnace is 1.01 times. The prepared carbon fiber has a skin-core ratio of 0%, an inner-outer diameter ratio E i It is 40% and the relative deviation is 8%.

[0050] Comparative Example 1

[0051] This comparative example is substantially the same as Example 3, except that the concentration of the coagulation bath is 55 wt % and the temperature of the coagulation bath is 23° C. The prepared raw silk has a flat structure and an inner and outer diameter ratio of E i The relative deviation is 58% and 67%.

[0052] Comparative Example 2

[0053] This comparative example is roughly the same as Example 3, except that the diameter of the needle in the needle-containing cylinder is 0.8 mm, the diameter of the micropores in the micropore-containing through hole is 1.2 mm, and the aspect ratio of the spinneret hole is 5:1. The prepared raw silk has a flat structure, and the inner and outer diameter ratio is E i The relative deviation is 53% and 20.9%.

[0054] Comparative Example 3

[0055] This comparative example is roughly the same as Example 3, except that the diameter of the needle in the needle-containing cylinder is 0.3 mm, the diameter of the micropores in the micropore-containing through hole is 0.5 mm, and the aspect ratio of the spinneret hole is 4:1. The prepared raw silk has a flat structure, and the inner and outer diameter ratio is E i The relative deviation is 34% and 43.3%.

[0056] Comparative Example 4

[0057] This comparative example is substantially the same as Example 3, except that the diameter of the needle in the needle-containing cylinder is 0.3 mm, the diameter of the micropore in the micropore through hole is 1.5 mm, and the aspect ratio of the spinneret hole is 3: 1. The prepared carbon filament is a solid structure with a skin-core ratio of 11.6%.

[0058] Comparative Example 5

[0059] This comparative example is roughly the same as Example 3, except that the pre-oxidized filaments are sequentially carbonized in a low-temperature furnace and a high-temperature furnace to prepare a carbon fiber with a hollow cross-section, the temperature of the low-temperature furnace is controlled at 650°C, the drafting ratio of the low-temperature furnace is 1.02 times, the temperature of the high-temperature furnace is controlled at 1650°C, and the drafting ratio of the high-temperature furnace is 1.01 times. The prepared carbon fiber has a skin-core ratio of 2%, an inner-outer diameter ratio of E i The relative deviation is 40% and 43%.

Claims

1. A method for preparing hollow cross-section polyacrylonitrile dry-jet wet-spinning carbon fiber, characterized in that: The following steps are involved: (1) Using 95-99 wt.% acrylonitrile as the first monomer and 1-5 wt.% acrylic acid, methyl acrylate, methyl methacrylate or isobutyl methacrylate as the second monomer, solution polymerization is carried out in dimethyl sulfoxide to obtain a spinning solution, and the temperature of the spinning solution is controlled to be 40-70°C and the solid content is 10-25%; (2) After the spinning solution is stripped and degassed, it is pressurized and extruded through a spinneret with an annular cavity, the extrusion speed is 10-20 m / min, and then enters a dimethyl sulfoxide coagulation bath through an air layer for coagulation phase separation to form gel strips, and is simultaneously drawn to obtain primary fibers with a hollow cross-section, the coagulation bath concentration is 30-50 wt%, and the coagulation bath temperature is 5-20°C; the spinneret with an annular cavity comprises a first plate body (1) and a second plate body (2); the first plate body (1) is provided with a plurality of through holes (4), a plurality of needle-containing cylinders (8), an annular groove (3) is provided on the top, and an annular groove (5) is provided on the bottom; the second plate body (2) is provided with a plurality of micropore through holes (9); the first plate body (1) and the second plate body (2) are bonded to form a slurry inlet channel (6); the needle-containing cylinders (8) on the first plate body correspond one to one with the micropore through holes (9) on the second plate body to form an annular cavity (7); the through hole (4) is connected to the pulp inlet channel (6), and the pulp inlet channel (6) is connected to the annular cavity (7); the annular groove (3) and the annular groove (5) are provided with rubber rings; the top of the first plate body (1) is pressed against the raw liquid feed pipe, and the top of the second plate body (2) is pressed against the bottom of the first plate body (1); the needle length of the needle-containing cylinder (8) is the same as the length of the micropores in the micropore-containing through hole (9), the needle diameter of the needle-containing cylinder (8) is 0.5-0.6 mm, and the micropore diameter of the micropores in the micropore-containing through hole (9) is 1.0-1.5 mm; the aspect ratio of the spinneret hole is 3-4:1; (3) The nascent fiber is washed with deionized water in multiple stages to remove the solvent, and then washed with hot deionized water and drawn; (4) The fibers after hot water drawing are oiled and then passed through hot rollers for drying and densification; (5) The dried and densified fibers enter steam drawing, and are wound after steam drawing to obtain hollow cross-section raw fibers; (6) The hollow section raw wire passes through the wire withdrawal rack and enters the pre-oxidation furnace for pre-oxidation to obtain pre-oxidized wire; (7) The pre-oxidized filaments are sequentially carbonized in a low-temperature furnace and a high-temperature furnace to prepare carbon fibers with a hollow cross-section; the temperature of the low-temperature furnace is 580-650°C, and the drafting ratio of the low-temperature furnace is 1.0-1.1 times; the temperature of the high-temperature furnace is 1450-1600°C, and the drafting ratio of the high-temperature furnace is 0.95-1.05 times.

2. The preparation method according to claim 1, characterized in that: In step (2), the method for degassing is as follows: first, the spinning solution is degassed at a pressure of -76KPa in a degassing kettle, and then it is filtered through a 3μm primary filter, and then it is degassed through a degassing kettle at a pressure of -97KPa, and then it is sent to a 1μm secondary filter for treatment.

3. The preparation method according to claim 1, characterized in that: In step (2), the air layer height is 1-5 mm, and the air drafting multiple is 1-2 times.

4. The preparation method according to claim 1, characterized in that In step (2), the coagulation bath concentration is 45 wt % and the coagulation bath temperature is 5° C.

5. The preparation method according to claim 1, characterized in that: In step (2), the number of holes in the through hole (4) is 1-2K, the number of holes in the needle-containing cylinder (8) and the number of holes in the micropore-containing through hole (9) are the same, both are 1-5K, the length of the needle in the needle-containing cylinder (8) and the length of the micropore in the micropore-containing through hole (9) are both 0.3-1.0 mm; the length of the cylinder in the needle-containing cylinder (8) is 10-15 mm, and the diameter of the cylinder is 3-5 mm; the length of the through hole in the micropore-containing through hole (9) is 5-8 mm, the through hole diameter is 4-6 mm, and the hole spacing is 1-3 mm; the spinneret with an annular cavity is made of Hastelloy C276, 316lL alloy, 1Cr18Ni9Ti austenitic stainless steel, AISI316 or AISI630.

6. The preparation method according to claim 1, characterized in that: In step (3), the water washing tank is 3 to 7 levels, the water washing temperature is 20 to 36°C, and the drafting ratio is 1 to 1.5 times; the hot desalted water washing and drafting are 1 to 3 stages, the temperature is 60 to 80°C, and the drafting ratio is 1 to 2.0 times.

7. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the hot roller is level 3 to level 7, the temperature range is 100 to 185°C, and the pressure of the hot roller is 0.30 to 1.10 MPa.

8. The preparation method according to claim 1, characterized in that: In step (5), the steam pressure is 0.30-0.80 MPa, the steam drawing ratio is 3.0-5.0 times, and the winding speed is 350-500 m / min.

9. The preparation method according to claim 1, characterized in that: In step (6), the pre-oxidation temperature is 200°C to 300°C, and the pre-oxidation stretching multiple is 0.9 to 1.05 times.

10. The preparation method according to claim 9, characterized in that: The pre-oxidation temperature is 220℃~240℃.

Citation Information

Patent Citations

  • Method for preparing polyacrylonitrile carbon fiber protofilament by dry and wet methods

    CN102146595A

  • Preparation method for novel warm-keeping type polyacrylonitrile hollow fiber

    CN103556282A

  • Method of using annular spinneret plate to manufacture dry-jet wet-spun polyacrylonitrile nascent fibers

    CN111647956A

  • Spinneret of convenient maintenance

    CN204589398U

  • Spinneret plate for preparing hollow-section carbon fibers

    CN223342879U